End-of-Life Care for Neonates: Assessing and Addressing Pain and Distressing Symptoms - Haug, Shelly; Dye, Alicia; Durrani, Sara (Frontiers in Pediatrics, 2020)
One of the most essential components of end-of-life (EOL) care for neonates is assessing and addressing distressing symptoms. There is limited evidence to guide neonatal EOL symptom management and therefore significant variety in treatment(1–4). EOL neonatal palliative care should include identifying and relieving distressing symptoms. Symptoms to manage at neonatal EOL may include pain using both non-pharmacologic and pharmacologic comfort measures, respiratory distress, secretions, agitation and neurologic symptoms, nutrition and gastrointestinal distress, and skin care. Also of equal importance is communication surrounding familial existential distress and psychosocial care (1,5–7). Institutions should implement a guideline for neonatal EOL care as guidelines have been shown to decrease variability of interventions and increase use of pharmacologic symptom management(4). Providers should consult with palliative care teams if available for added multidisciplinary support for family and staff which has shown to enhance EOL care in neonates(8,9).